2010
DOI: 10.4319/lom.2010.8.484
|View full text |Cite
|
Sign up to set email alerts
|

Tracer Additions for Spiraling Curve Characterization (TASCC): Quantifying stream nutrient uptake kinetics from ambient to saturation

Abstract: Stream nutrient tracer additions and nutrient spiraling metrics are frequently used to quantify lotic ecosystem behavior. Of particular concern is the influence nutrient concentration exerts on nutrient retention and export. However, characterizing spiraling response curves across a range of concentrations has remained challenging, in part due to the large effort required to develop these curves using traditional (e.g., plateau or steadystate) approaches. Here we outline and demonstrate a new approach to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
182
2
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(195 citation statements)
references
References 26 publications
4
182
2
7
Order By: Relevance
“…We conclude that while this method may enable important refinements in the spatial ecology and biogeochemistry of rivers, it may not ultimately yield unequivocal inference of kinetics due to small longitudinal concentration gradients that arise within most rivers, and due to the confounding effects of temporally varying removal. Other methods may be better suited, though we note comparing multiple injections (Payn et al 2005) performed at different times of day or even single pulse injections (Covino et al 2010) in long-residence-time systems may also require adjustment for time-varying removal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We conclude that while this method may enable important refinements in the spatial ecology and biogeochemistry of rivers, it may not ultimately yield unequivocal inference of kinetics due to small longitudinal concentration gradients that arise within most rivers, and due to the confounding effects of temporally varying removal. Other methods may be better suited, though we note comparing multiple injections (Payn et al 2005) performed at different times of day or even single pulse injections (Covino et al 2010) in long-residence-time systems may also require adjustment for time-varying removal.…”
Section: Discussionmentioning
confidence: 99%
“…In this ''efficiency-loss model,'' removal is a power function of concentration. Other recent work using plateau (Earl et al 2006) and pulse additions (Covino et al 2010) to assess reaction kinetics has suggested Michaelis-Menten (MM) kinetics where removal becomes completely saturated at high concentration. Empirically resolving controls on removal kinetics in time and space, with network position and in a way that is pathway specific (i.e., assimilation vs. denitrification), is an important priority, with implications for understanding river responses to nutrient enrichment (Mulholland et al 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…/jwld-2016 by MOŢOC et al [1975], IONIŢĂ et al [2006], MIRCEA et al [2010;, MAETENS et al [2012]; hydrological: PETRESCU [1974], STANCIU [2002], YU et al [1997], BENAVIDES-SOLORIO, MACDONALD [ , JOEL et al [2002; forestry by ABAGIU et al [1973], HARTANTO et al [2003]; biological factors [WAIN-WRIGHT et al 2000]; ecologic by GBUREK and SHAR-PLEY [1998], DEBANO [2000], COVINO et al [2010], ATUCHA et al [2013].…”
Section: Introductionmentioning
confidence: 99%